Selective fluorescent chemosensors and iodinated contrast agents : biological evaluation for cellular zinc detection, microdamage detection and imaging - Parkesh, Raman (Trinity College (Dublin, Ireland). School of Chemistry, 2004)
This thesis entitled "Selective Fluorescent Chemosensors and lodinated Contrast Agents: Biological Evaluation for Cellular Zinc detection, Microdamage Detection and Imaging" has been divided into six Chapters. Chapter 1 highlights advances made in the field of fluorescent chemosensors. Examples discussed have been critically evaluated in terms of their photophysical properties, selectivity, sensitivity and binding ability. To introduce the relevance of supramolecular systems for microdamage detection in bone, a brief introduction to the characteristics of bone and X-rays are also provided. Chapter 2 presents in detail the design, synthesis and photophysical evaluation of two water soluble and selective Zn(II) fluoroprobes 92 and 93. The key feature of these sensors is their stability under simulated physiological conditions. The fluorescence titrations of 92 demonstrated its ability to detect nanomolar free Zn(II). Preliminarily studies carried out using pancreatic tissue have shown the ability of 92 to label the areas, which contain chelatable zinc. Chapter 3 presents in details two aqueous soluble, anthracene based fluorescent PET sensors 125 and 126 for selective recognition of Zn(II) and Cd(II). The evaluation of the photophysical response o f these sensors demonstrated their ability to distinguish between Zn(II) and Cd(II). Chapter 4 details a critical investigation of microdamage in bone using histological methods, SEM and EDXA. A set of fluoroprobes, 135, 136, 138, 140, 141, 142, 143, 92, 93 and 125 were used to investigate the selective labelling of the microcrack in the bone. The scratched and unscratched surfaces of the bone were studied using Raman spectroscopy, SEM and EDXA. The selective labelling of scratches observed can be attributed to the interaction of dyes via binding at the free lattice sites, ionic interactions with the free lattice sites or incorporation in the broken lattice sites.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin